Adding a dose of empathy to healthcare: What can healthcare systems do?. Issue 3 (25th February 2022) - Kang, Esther ShinHyun; Di Genova, Tanya; Howick, Jeremy; Gottesman, Ronald
Abstract: Rationale, Aims and Objectives: Healthcare practitioners often note system‐level barriers to empathy between patients and practitioners. These include burnout‐inducing administrative workloads, unfriendly meeting times, burdensome protocols, lack of wellbeing spaces, and undervaluing empathy as a core part of an institution's mission. The need for empathy in healthcare has been magnified with the current SARS‐COV‐2 outbreak which has limited the expression of interpersonal empathy due to rigid isolation protocols and the use of personal protective equipment. Method: This study—the first of its kind that we are aware of—outlines the details of a facilitated workshop run with the leadership of a tertiary level pediatric center in Canada. The workshop used a modified nominal group technique to discuss and prioritize actions to enhance empathy into the hospital system. Results: Inter‐professional and inter‐disciplinary group of healthcare leader participants agreed on several immediately actionable steps, including embedding patient satisfaction with care measures as standard, and streamlining booking appointments. A roadmap was created to implement the other priorities. Conclusion: A systematic approach to infusing empathy into the structure of our healthcare system is much needed. Furthermore, inter‐professional and inter‐disciplinary educational workshops was well‐received as a way to facilitate discussion and drive change.